2014
DOI: 10.1007/s00213-014-3561-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of the D1 receptor for the dopamine agonist-induced one-trial behavioral sensitization of preweanling rats

Abstract: Rationale The neural mechanisms mediating the ontogeny of behavioral sensitization are poorly understood. Objective The purpose of the present study was to determine the role of the D1 receptor for the induction of dopamine agonist-induced behavioral sensitization during the preweanling period. Methods In the first experiment, the early ontogeny of NPA-induced behavioral sensitization was examined by pretreating male and female rats with saline or NPA (0.5, 1, or 2 mg/kg, IP) before placement in activity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
1
7
1
Order By: Relevance
“…Using a one-trial protocol, researchers testing adult rats and mice have reported that D1 (Fontana et al 1993; Valjent et al 2010) and D2 receptor antagonists (Weiss et al 1989; Fontana et al 1993) block psychostimulant-induced behavioral sensitization. Conversely, neither D1 nor D2 receptor antagonists prevent the induction of methamphetamine sensitization in preweanling rats (present study; Mohd-Yusof et al 2014). This pattern of results suggests that the neural mechanisms underlying the induction of behavioral sensitization, perhaps including the availability of ‘redundant pathways’, differs between early ontogeny and adulthood.…”
Section: Resultscontrasting
confidence: 66%
See 4 more Smart Citations
“…Using a one-trial protocol, researchers testing adult rats and mice have reported that D1 (Fontana et al 1993; Valjent et al 2010) and D2 receptor antagonists (Weiss et al 1989; Fontana et al 1993) block psychostimulant-induced behavioral sensitization. Conversely, neither D1 nor D2 receptor antagonists prevent the induction of methamphetamine sensitization in preweanling rats (present study; Mohd-Yusof et al 2014). This pattern of results suggests that the neural mechanisms underlying the induction of behavioral sensitization, perhaps including the availability of ‘redundant pathways’, differs between early ontogeny and adulthood.…”
Section: Resultscontrasting
confidence: 66%
“…In terms of the present study, it is also possible that redundant pathways, perhaps involving the 5-HT or adrenergic system, may mediate the induction of one-trial behavioral sensitization in preweanling rats. Such redundant pathways would explain why neither SCH23390 (Mohd-Yusof et al 2015) nor raclopride (present study) blocked the initial induction of methamphetamine-induced one-trial behavioral sensitization in preweanling rats. On first appraisal, methamphetamine’s mechanism of action and selectivity at monoamine transporters may seem to argue against a ‘redundant pathway’ explanation.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations